2015
DOI: 10.1111/cxo.12210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for symptomatic dry eye disease in Singapore

Abstract: Background:The aim of this study was to describe the prevalence and risk factors of symptomatic dry eye disease (SDED) in Singapore. Methods: A cross-sectional dry eye survey was carried out using the McMonnies dry eye questionnaire. Members of the public were interviewed at the 46 (out of 62) randomlyselected mass rapid transit (MRT) stations and their vicinity. A total of 1,004 questionnaires were collected from participants aged between 15 and 83 years. Symptomatic dry eye disease (SDED) was defined as at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 47 publications
4
80
0
10
Order By: Relevance
“…Univariate logistic regression analysis showed that females were 1.39 times likely to have dry eye, which was statistically significant but was not statistically significant in the multivariate analysis. This is consistent with Tan et al 4 and many other studies 3,20,25 who also reported a higher prevalence in females compared to males.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Univariate logistic regression analysis showed that females were 1.39 times likely to have dry eye, which was statistically significant but was not statistically significant in the multivariate analysis. This is consistent with Tan et al 4 and many other studies 3,20,25 who also reported a higher prevalence in females compared to males.…”
Section: Discussionsupporting
confidence: 93%
“…1 Dry eye symptoms comprise dryness, ocular pain, burning, visual disturbance, eye fatigue, grittiness, photophobia, soreness, irritation, tearing, and others. [2][3][4] Dry eye is among the most prevalent ophthalmic disease. It is reported that intolerance of dry eye symptoms accounts for its impact on public health and the eye care seeking mannerism of dry eye patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contact lens wear increases the risk of developing dry eye from between 2.01 and 2.96 times [580582]. Contact lenses compartmentalize the tear film into two layers; the outer pre-lens tear film layer in front of the lens, and the inner post-lens tear film layer, which lies between the lens and the cornea [583,584].…”
Section: Non-pathophysiological Factors Impacting the Tear Filmmentioning
confidence: 99%
“…Es una enfermedad multifactorial de la superficie ocular que afecta a la película lagrimal provocando su inestabilidad, dando como resultado síntomas de malestar ocular, alteraciones visuales y un potencial daño de las estructuras oculares externas 2 . La prevalencia de la enfermedad ha sido ampliamente estudiada con resultados muy variables, desde el 5% hasta más del 70% en personas mayores de 50 años 1,[3][4][5][6][7][8][9][10][11][12][13] ; los resultados varían de acuerdo con la definición utilizada, los métodos diagnósticos y la población estudiada 1 . El cuestionario del Índice de Enfermedad de la Superficie Ocular (OSDI, por sus siglas en inglés) es un método muy utilizado en estudios epidemiológicos de ojo seco y enfermedad de la superficie ocular, ya que evalúa por medio de 12 preguntas no solo la sintomatología asociada a esta enfermedad, sino también el impacto en la calidad de vida de los encuestados.…”
Section: Introductionunclassified